Efficacy and safety of inclisiran in patients with polyvascular disease: pooled, post hoc analysis of the ORION-9, ORION-10 and ORION-11, phase 3 randomised controlled trials. (14th October 2021) - Koenig, W; Ray, K K; Kallend, D G; Landmesser, U; Leiter, L A; Schwartz, G G; Wright, R S; Garcia Conde, L; Jaros, M; Raal, F J
Abstract: Background: Approximately 25% of patients (pts) with atherosclerotic cardiovascular disease (ASCVD) have polyvascular disease (PVD), which involves ≥2 coronary, cerebrovascular, and peripheral artery beds. PVD is an independent predictor of major adverse cardiovascular (CV) events (MACE) and death.[1, 2] Agents that inhibit proprotein convertase subtilisin-kexin type 9 (PCSK9) resulted in reduced low-density lipoprotein cholesterol (LDL-C) concentration and MACE incidence in pts with PVD.[3, 4] Inclisiran is a small interfering RNA (siRNA) agent targeting PCSK9 messenger RNA that provided effective and sustained reduction in LDL-C concentration and was well tolerated.[5] Purpose: To describe the effect inclisiran versus placebo (pbo) in pts with and without PVD. Methods: This was a post hoc analysis from the ORION-9 (NCT03397121), ORION-10 (NCT03399370) and ORION-11 (NCT03400800) trials. Pts with heterozygous familial hypercholesterolaemia, ASCVD or risk equivalents were randomised 1:1 to receive 300 mg inclisiran sodium (equivalent to 284 mg inclisiran) or pbo at baseline, Day 90, and 6-monthly thereafter. LDL-C percentage change from baseline to Day 510 and corresponding time-averaged change from Day 90 and to Day 540 were evaluated by presence or absence of PVD (intention-to-treat population). Safety was assessed over 540 days (safety population). Results: Of 3454 pts, 470 (13.6%) had PVD and 2984 (86.4%) did not. Baseline characteristics were generally balanced between treatment arms in both groups (Table 1). A greater proportion of pts with vs without PVD had CV risk factors at baseline. Mean LDL-C concentration at baseline was lower in pts with vs without PVD (Table 1). Mean (95% CI) pbo-corrected LDL-C percentage change from baseline to Day 510 with inclisiran was −48.9 (−55.6 to −42.2) in pts with PVD and −51.5 (−53.9 to −49.1) in pts without PVD (Table 2). Proportions of pts with treatment-emergent adverse events (TEAE) and treatment-emergent serious adverse events (TESAE) were similar between treatment arms irrespective of PVD status although reported TESAEs were numerically greater in both treatment arms for pts with PVD (Table 2). Clinically relevant TEAEs at the injection site were reported more frequently with inclisiran vs pbo in both groups but all were mild or moderate (Table 2). Proportions of pts with clinically relevant laboratory measurements were low and similar between treatment arms for both groups (Table 2). Conclusions: Twice-yearly dosing with inclisiran (after the initial and 3-month doses) provided effective and sustained LDL-C lowering in pts, irrespective of their PVD status, with a safety profile similar to pbo, except for a modest excess of mainly mild TEAEs at the injection site. Notably, TESAEs were reported more frequently in pts with PVD, which was likely due to their more advanced disease. Since pts with PVD are at high risk of CV events, intensive LDL-C lowering may be beneficial to reduce this risk. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Novartis Pharma AG, Basel, Switzerland